Jual Beli Barang Curian Ditinjau Dari Perspektif Hukum Islam dan Hukum Pidana - Abdurrahman; Febrian, Arman; Ridwan, Muhammad (Tabayyun : Journal Of Islamic Studies, 2024)
This paper discusses the legal status of stolen goods, whether they are stolen goods unknown to the buyer or stolen goods that were fully known to the buyer but he was still unsure whether the item was stolen or not. To answer this The problem is that the author uses quantitative methods using literature or libraries approach, in this case the author seeks answers from various jinayah fiqh books. The findings in this article are that the practice of buying and selling is stolen goods are strictly prohibited in Islam, especially buying goods with status it is clearly known to be a product of theft or it is not clearly known, but there are indications that point to stolen goods, then it is unlawfull to buy them even if they are priced at a relatively cheap price.